Biotransformation of vanillin into vanillyl alcohol by a novel strain of Cystobasidium laryngis isolated from decaying wood - Rönnander, Jonas; Ljunggren, Joel; Hedenström, Erik; Wright, Sandra Ann Ingela (AMB Express, 2018)
Vanillin is an aromatic aldehyde found as a component of lignocellulosic material, and in the cured pods of orchidaceae plants. Like other phenolic substances, vanillin has antimicrobial activity and can be extracted from lignin either by a thermo-chemical process or through microbial degradation. Vanillin, can serve as a model monomer in biodegradation studies of lignin. In the present study, a yeast isolated from decaying wood on the Faroe Islands, was identified as Cystobasidium laryngis strain FMYD002, based on internal transcribed spacer sequence analysis. It demonstrated the ability to convert vanillin to vanillyl alcohol, as detected by ultra-high performance liquid chromatography-quadrupole-time-of-flight. Structural analysis of vanillyl alcohol was carried out by using gas chromatography-mass spectrometry and H-1 NMR spectroscopy, and further verified by synthesis. The reduction of vanillin to vanillyl alcohol has been documented for only a few species of fungi. However, to our knowledge, this biotransformation has not yet been reported for basidiomycetous yeast species, nor for any representative of the subphylum Pucciniomycotina. The biotransformation capability of the present strain might prove useful in the industrial utilisation of lignocellulosic residues.